2018
DOI: 10.1039/c8cp00160j
|View full text |Cite
|
Sign up to set email alerts
|

Cerium oxide immobilized reduced graphene oxide hybrids with excellent microwave absorbing performance

Abstract: Microwave absorbing materials with high absorption over a broad bandwidth when they have a small thickness are strongly desired due to their widespread applications. Herein, cerium oxide immobilized reduced graphene oxide (CeO2-rGO) hybrids with excellent microwave absorbing performance have been fabricated by a versatile one-step hydrothermal approach. Modern measurement techniques, including X-ray diffraction, Raman spectroscopy, electronic microscopy, X-ray photoelectron spectroscopy and vector network anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 59 publications
0
39
0
1
Order By: Relevance
“…The average crystallite sizes of CeO 2 NPs and CeO 2 -RGO nanocomposites were estimated by Scherrer's formula, using the prominent peak (111), and it was found to be around 18 and 16 nm for CeO 2 NPs and CeO 2 -RGO nanocomposites, respectively. Our XRD data on RGO, CeO 2 NPs, and CeO 2 -RGO nanocomposites were according to earlier reports [36,37]. estimated by Ellman's procedure, using 5,5-dithio-bis-nitrobenzoic acid (DTNB) [33].…”
Section: Characterization Of Ceo 2 Nps Rgo and Ceo 2 -Rgo Nanocomposmentioning
confidence: 99%
See 1 more Smart Citation
“…The average crystallite sizes of CeO 2 NPs and CeO 2 -RGO nanocomposites were estimated by Scherrer's formula, using the prominent peak (111), and it was found to be around 18 and 16 nm for CeO 2 NPs and CeO 2 -RGO nanocomposites, respectively. Our XRD data on RGO, CeO 2 NPs, and CeO 2 -RGO nanocomposites were according to earlier reports [36,37]. estimated by Ellman's procedure, using 5,5-dithio-bis-nitrobenzoic acid (DTNB) [33].…”
Section: Characterization Of Ceo 2 Nps Rgo and Ceo 2 -Rgo Nanocomposmentioning
confidence: 99%
“…The XPS spectra of C1s given in Figure 2B contain a non-oxygenated aromatic sp 2 bonded carbon ring (C-C) at 286.5 eV [39]. Figure 2C represents the O1s spectra of CeO2, with two intense peaks at 530.9 and 536.8 eV, linked with anionic oxygen in CeO2 and the presence of the residual oxygen functional group in the RGO sheets, respectively [37]. The morphologies of the CeO2 NPs, RGO, and CeO2-RGO nanocomposites were further characterized by SEM and TEM ( Figure 3A-F).…”
Section: Characterization Of Ceo2 Nps Rgo and Ceo2-rgo Nanocompositesmentioning
confidence: 99%
“…The D band and the G band located at 1334.1 and 1588.9 cm −1 for RGO, 1337. 5 [38] The integrated area ratio (I D /I G ) of these two peaks varied from 1.53 to 1.77 ( Figure 4b), which may be attributed to more numerous defects created during the combination of CeO 2−x and RGO. [39][40][41] Importantly, these defective sites which would induce charge polarization relaxation were deeply related to the MA performance.…”
Section: Structure Characterization Of Accordion-like Ceo 2−x /Rgo Comentioning
confidence: 99%
“…[30] Wang et al fabricated RGO/CeO 2 composites which showed enhanced MA performance. [31] Gao et al synthesized a series of 2D carbonbased nanocomposites with the loading of cerium oxide and other types of rare earth oxides with tunable and ultra-efficient MA properties. [32] These studies guide us to tune the correlative electromagnetic properties of composite by simply regulating one of the two components.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 For years, researchers have been focusing on developing light weight and effective absorber with strong reection loss and broad absorbing bandwidth. 8,9 In the last few years, various carbonaceous materials have always been ideal candidates for EMW absorbing materials due to their controllable structure and properties. Particularly, graphene oxide (GO), carbon nanotubes (CNT), as well as their derivatives, have made great progress as precursors of EMW absorbing materials.…”
Section: Introductionmentioning
confidence: 99%